2014
DOI: 10.1542/peds.2013-1820
|View full text |Cite
|
Sign up to set email alerts
|

Management of Febrile Neonates in US Pediatric Emergency Departments

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Recommended management of febrile neonates (#28 days) includes blood, urine, and cerebrospinal fluid cultures with hospital admission for antibiotic therapy. No study has reported adherence to standard recommendations in the management of febrile neonates in US pediatric emergency departments. WHAT THIS STUDY ADDS:There is wide variation in adherence to recommended management of febrile neonates. High rates of serious infections in admitted patients but low return rates for missed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
100
3
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 19 publications
7
100
3
8
Order By: Relevance
“…First, the prevalence of SBI obtained in our study was similar to those reported in other recent European publications, 17,25,33 5 only 62% of the respondents reported using some set of published guidelines and among them, 20% cited using the Philadelphia protocol, 15% the Rochester criteria, and 13% the Boston criteria. As there seems to be no predominant criteria used in the United States and none of these classic risk criteria are frequently used in Europe, we chose the Rochester criteria for the reasons previously mentioned.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, the prevalence of SBI obtained in our study was similar to those reported in other recent European publications, 17,25,33 5 only 62% of the respondents reported using some set of published guidelines and among them, 20% cited using the Philadelphia protocol, 15% the Rochester criteria, and 13% the Boston criteria. As there seems to be no predominant criteria used in the United States and none of these classic risk criteria are frequently used in Europe, we chose the Rochester criteria for the reasons previously mentioned.…”
Section: Discussionsupporting
confidence: 89%
“…Regardless of the protocol used, current adherence to any of them in clinical practice is low. 4,5 Changes in the epidemiology of bacterial pathogens in the last decades 6,7 and introduction of biomarkers such as C-reactive protein (CRP) and, more recently, procalcitonin (PCT) could justify this low adherence rate and make several authors advocate for a more individualized approach. The latter includes new biomarkers and a reduction in lumbar puncture rates, antibiotic treatments, or in-hospital admission for many well-appearing infants outside the neonatal period.…”
mentioning
confidence: 99%
“…On the other hand, UTI was found higher and reported that 14-21.3 percent in febrile neonatesthat means UTI affects approximately 1 in 6 febrile neonates [2][3][4][5][6][7][8][9][10][11]18]. In our study, UTI incidence was found similarly the most common etiology of fever in neonatal period.…”
Section: Discussionsupporting
confidence: 47%
“…The causes of fever in these neonates vary from dehydration, mild viral infection to serious bacterial infections which are progressive and lead to severe morbidity or mortality. Evaluation and treatment of febrile neonatesvaried widely among the different centers [11]. These differences demonstrate the deficiency of and highlight the necessity for national or international guidelines for the assessment of fever in this age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation